The Critical Importance of Citizen Science Data - de Sherbinin, Alex; Bowser, Anne; Chuang, Tyng-Ruey; Cooper, Caren; Danielsen, Finn; Edmunds, Rorie; Elias, Peter; Faustman, Elaine; Hultquist, Carolynne; Mondardini, Rosy; Popescu, Ioana; Shonowo, Adenike; et al. (Frontiers in Climate, 2021)
Citizen science is an important vehicle for democratizing science and promoting the goal of universal and equitable access to scientific data and information. Data generated by citizen science groups have become an increasingly important source for scientists, applied users and those pursuing the 2030 Agenda for Sustainable Development. Citizen science data are used extensively in studies of biodiversity and pollution; crowdsourced data are being used by UN operational agencies for humanitarian activities; and citizen scientists are providing data relevant to monitoring the sustainable development goals (SDGs). This article provides an International Science Council (ISC) perspective on citizen science data generating activities in support of the 2030 Agenda and on needed improvements to the citizen science community’s data stewardship practices for the benefit of science and society by presenting results of research undertaken by an ISC-sponsored Task Group.